Faktor yang Mempengaruhi Penggunaan Metode Kontrasepsi Implant terhadap Minat Ibu - Jamuddin, Fatimah; Fitriani, Fitriani; Sulaeman, Sulaeman (Universitas Muhammadiyah Gresik, 2023)
ABSTRACT The population problem is a problem faced by all countries, both in developed and developing countries, including Indonesia. This can be seen from the very rapid growth in world population with a high growth rate. To reduce the rate of population growth. Mother's interest in using contraception is influenced by several factors, including knowledge, education, affordability of health services, husband's support. This type of research used a cross sectional study with a non-probability sampling technique with a purpposive sampling type of 46 samples that met the inclusion criteria. Data collection techniques are primary data by direct observation of respondents and questionnaires as an instrument using an observation approach. Data analysis used a questionnaire validity and reliability test, univariate and bivariate analysis. The results obtained from 46 respondents, 30 (65%) respondents with good interest and 16 (35%) respondents with less interest. There were 36(78.2%) respondents who were first users of implants and 10(21.8) were repeat users. 35 (76%) respondents with good knowledge and 11 (24%) with less knowledge. Based on education, there were 29 (63%) with higher education and 17 (37%) with lower education. Based on bivariate analysis using statistical tests, there is a significant relationship between maternal interest and implant contraceptive users, with a significance value (P) = 0.009 where P <0.05. there is a significant relationship between mother's interest and knowledge with a significance value (P) = 0.021 where P <0.05. There is a significant relationship between mother's interest in education, with a significance value (P): 0.000 where P <0.05